Phyto-evaluation of Cd-Pb Using Tropical Plants in Soil-Leachate Conditions - Ng, Chuck Chuan; Boyce, Amru Nasrulhaq; Rahman, Md Motior; Abas, Mhd Radzi; Mahmood, Noor Zalina (SAGE Publications, 2018)
Sources of soil contamination can exist in various types of conditions including in the form of semifluids. In this study, 3 different types of tropical plants, Acacia (Acacia mangium Willd), Mucuna (Mucuna bracteata DC. ex Kurz) and Vetiver (Vetiveria zizanioides L. Nash), were tested under different levels of soil-leachate conditions. The relative growth rate, metal tolerance, and phytoassessment of cadmium (Cd) and lead (Pb) accumulation in the roots and shoots were determined using flame atomic absorption spectrometry. Tolerance index, translocation factor, metal accumulation ratio, and percentage metal efficacy were applied to assess the metal translocation ability among all the 3 types of plants. Significantly higher (P < .05) accumulation of Cd and Pb was exhibited in the roots and shoots of all 3 plants growing under the soil-leachate conditions. However, negative growth performance and plant withering were observed in both Acacia and Mucuna with increased application of higher soil-leachate levels. Vetiver accumulated remarkably higher total concentration of Cd (116.16-141.51 mg/kg) and Pb (156.37-365.27 mg/kg) compared with both Acacia and Mucuna. The overall accumulation trend of Cd and Pb in the 3 plants growing under the soil-leachate conditions was in the order of Vetiver > Acacia > Mucuna. The findings of the study suggest that Vetiver has great potential as Cd and Pb phytoremediator in soil-leachate conditions.